Differences in Parameters of an Embryo In Vitro Production Program between Cattle (Bos Indicus) and Buffaloes (Bubalus bubalis) - Berdugo, Jesús Alfredo; Tarazona-Morales, Ariel Marcel; Echevererry, José Julian; Konrad, Jose Luis; Crudeli, Gustavo Angel; Lopéz-Herrera, Albeiro (Journal of Buffalo Science, 2020)
In order to improve production, it is necessary to apply reproductive biotechnologies, including embryo transfer. Due to the management and physiology of the animals and the buffalo production system, the best system is the in vitro production of embryos (IVP). This work aims to compare the results of the (IVP) of cows (Bos indicus) and buffalo (Bubalus bubalis) from animals kept under the same conditions of feeding and handling. This study was conducted in an Argentinan commercial herd located in the province of Corrientes (-27.742859 latitude, -57.773611 longitude) that raise buffaloes and cattle, during the breeding season of 2018 (March-May). Twenty animals of each species were used. Antimullerian hormone (AMH) levels of each animal were determined using ELISA. Standardized protocols were used for oocyte aspiration, maturation, fertilization and culture of the embryos, frozen semen of a single proved bull was used in each species. Information about the number of follicles, oocytes, and embryos was recorded and analyzed individually and grouped by species. The normality of the data was evaluated with the D’Agostino and Shapiro-Wilk tests and the comparisons between species using the Mann Whitney and ANOVA tests. Values are shown as median and range. A p-value <0.05 was considered statistically significant. The AMH levels of the cows were 688.5 pg/ml (45.3-2394) and the buffaloes 73.8 pg/ml (14.8-262.5), p <0.001. Significant differences were found in the number of recovered oocytes 9 (0-23) cows vs. 4.5 (1-11) buffaloes (p> 0.05). There were no significant differences in the number of follicles and the quality of the oocytes. Significant differences were found in the number of oocytes cleaved 4 (0 -17) vs. 0.5 (0-4) and blastocysts/animal 1,5 (0-15) and 0,1 (0-2) l for cows and buffalos respectively. The number of blastocysts in relation to the number of oocytes cleaved did not show statistical significance. The differences in the levels of AMH and the marked differences in the IVP between buffaloes and cattle are confirmed, it is necessary to propose research proposals that explain the differences.